2010
DOI: 10.1007/s10384-010-0828-7
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour ocular hypotensive effects of 0.0015% tafluprost and 0.005% latanoprost in healthy subjects

Abstract: The overall efficacies of the two agents were not different, but tafluprost was associated with a greater reduction in IOP at 24 h after administration. Tafluprost showed a higher rate of conjunctival hyperemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…Therefore, we used normal subjects for this study. Fortunately, PGAs caused a considerable IOP reduction in the normal subjects in this study, which was comparable to previous studies with normal subjects [9,21], and a different profile of IOP reduction with bimatoprost compared to latanoprost clearly appeared. Given that non-responders are more frequent in patients with low baseline IOPs, the data with normal subjects may be useful for patients with normal-tension glaucoma.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, we used normal subjects for this study. Fortunately, PGAs caused a considerable IOP reduction in the normal subjects in this study, which was comparable to previous studies with normal subjects [9,21], and a different profile of IOP reduction with bimatoprost compared to latanoprost clearly appeared. Given that non-responders are more frequent in patients with low baseline IOPs, the data with normal subjects may be useful for patients with normal-tension glaucoma.…”
Section: Discussionsupporting
confidence: 85%
“…42 The differences in day/night lowering of PF-tafluprost versus latanoprost were also similar to those of a study in 30 healthy individuals in Japan in which the mean difference in IOP between the two drugs was 0.1 mmHg. 43 The results were also consistent with previous experience showing good tolerability for PFtafluprost. 6,7 In this study, therefore, PF-tafluprost showed similar efficacy but improved tolerability compared with latanoprost.…”
Section: Anton Hommersupporting
confidence: 90%
“…Apart from the differences in study populations and despite several methodological differences (timing of drug administration, duration of therapy and different time of IOP measurements), it is interesting to note the similarities in findings between the two 24 h studies. The Mochizuki study25 also observed a mean 24 h difference of 0.1 mm Hg and the two prostaglandins exhibited similar tendencies to preferentially lower IOP during the day (latanoprost) and night (tafluprost). In contrast with the present study, however, these IOP lowering differences reached statistical significance in the Japanese study.…”
Section: Discussionmentioning
confidence: 73%
“…Thus the present study highlights the value of a complete efficacy assessment over 24 h in determining the true IOP lowering characteristics of a novel antiglaucoma medication. In a previous 24 h IOP study in 30 healthy Japanese subjects, Mochizuki et al compared the efficacy of tafluprost and branded latanoprost 25. Apart from the differences in study populations and despite several methodological differences (timing of drug administration, duration of therapy and different time of IOP measurements), it is interesting to note the similarities in findings between the two 24 h studies.…”
Section: Discussionmentioning
confidence: 99%